Smile - Telgemeier, Raina; yue, stephanie (New York Scholastic, 2010)
Raina Telgemeier's #1 New York Times bestselling, Eisner Award-winning graphic memoir based on her childhood!
Comic strips
2
Keywords: Girls -- Dental care; Self-esteem in adolescence